Unification of the Law of Carriage of Passengers in the European Union - Myth or Reality? - Dorota AMBROZUK (Communications of International Proceedings, 2020)
Under a common transport policy and consumer policy, beginning in the 1990s, European Union’s bodies have been issuing regulations governing the subject-matter of the carriage of passengers. Their aim was to uniform the rules applicable in this scope in European Union Member States, and at the same time to raise the level of passenger protection with regard to regulations already included in international carriage conventions and domestic laws in individual Member States (cf. Gospodarek, 2011, pp. 55-68; see also Kersten, 2007, pp. 117-136). Solutions that were more favourable to passengers compared to the existing ones have been introduced. Issues not previously legislated have been regulated. The Union’s legislator maintained at that (modelled on international carriage conventions) the branch-like nature of these regulations (cf. Ambrożuk, 2014, pp. 11-24). Even though provisions of individual carriage regulations address an array of issues, they still do not comprehensively regulate problems that a passenger may face while travelling. Certain issues are still not standardised and Member States were left with considerable freedom when it comes to other matters. In this state of facts, it is reasonable to ask whether unification of the law of carriage of passengers has indeed been achieved. The aim of this paper is to provide an answer to this question. The author presents issues which need to be regulated at the Union level to bring about full, or at least further reaching, unification. The author analyses legislation and judicial decisions, including those of the CJEU, and reviews the literature.
Keywords: European Union law; carriage of passengers; unification of regulation